Apprehending the Culprits: The Discourse of Anti-Profiteering and Law Enforcement in Goods and Services Tax (GST) News Reports - Ong Cheng Teik; Hajar Abdul Rahim (Kajian Malaysia, 2019)
A series of false starts and deferments since the 1980s preceded the eventual implementation of the goods and services tax (GST) in Malaysia on 1 April 2014 amidst adverse economic conditions, public resentment and hostility from certain quarters. In order to neutralise such negative reception, the former Barisan Nasional (BN) government embarked on a series of initiatives, programmes and campaigns to educate the public on the benefits of the GST to the country, one of which was the setting up of GST Malaysia Info, a website whose original aim was to disseminate positive news and to promote the GST to the public. As the recent implementation of the GST bore on all sections of the Malaysian society, a Critical Discourse Analysis (CDA) of selected news articles on the website was carried out to uncover the various discourses related to the GST to portray the government’s position on the issue of the GST. The paper will present part of the findings of a larger study related to the discourse of anti-profiteering and law enforcement and the representation of its attendant aspects and circumstances. Predicated on Fairclough’s (1989; 2001; 2015) Critical Discourse Analysis, the study sheds light on the mainstream media’s favourable representation of the former BN government and its machinery and pejorative representation of the GST perpetrators and offenders through the use of lexical words with experiential values.